Addressing poverty and inequality in Viet Nam during the COVID-19 pandemic: An examination of the alleviating impact of tax and benefit measures - Antoine de Mahieu; Jesse Lastunen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates the impact of the COVID-19 pandemic and related tax-benefit measures in Viet Nam. The focus is on the initial phase of the crisis in 2020. The study delves into how the pandemic affected disposable incomes, examining the differences across the income distribution and impacts on measures of poverty and inequality. The paper also evaluates the effectiveness of tax-benefit policies in reducing income losses caused by the pandemic, covering both the automatic stabilization of the pre-existing tax-benefit system and discretionary policy measures adopted in response to the crisis. The findings suggestthat disposable incomes decreased by nearly 2.25 per cent on average, with the most pronounced effect experienced by higher-income households. Additionally, the estimates point to moderate increases in both the headcount poverty rate and the extent of poverty, as measured by the poverty gap. Automatic stabilizers had a limited effect in cushioning the income shock. The discretionary social protection measures, however, halved the pandemic-induced rise in the national poverty rate and fully reversed income losses for the poorest income quartile.
Keywords: D31; E24; H24; 330; COVID-19; income distribution; poverty; inequality; Viet Nam